Explaining the psychological distress of women with high-risk pregnancies in Iran: A qualitative study - Solmaz Mohammadi; Kobra Shojaei; Elham Maraghi; Zahra Motaghi (Iranian Journal of Nursing and Midwifery Research, 2022)
Background: Psychological Distress (PD) is one of the most common mental disorders during pregnancy and involves stress, anxiety, and depression. According to the literature, High-Risk Pregnancy' (HRP) is a major physiological risk factor associated with PD during pregnancy. The main purpose of this study was to explore the perception and experience of women with HRP who, based on standard questionnaires, had moderate-to-severe stress and anxiety scores. Materials and Methods: This qualitative study was conducted using conventional content analysis from December 2020 to June 2021. To this aim, 16 women with HRP were purposefully selected from Imam Khomeini Hospital in Ahvaz, Iran, with maximum diversity. In-depth, semi-structured, individual interviews were conducted to collect the data. The MAXQDA software was used for data analysis. Results: Data analysis led to the extraction of two main categories and nine subcategories. “Disrupted peace” and “inefficient adaptation to the situation” were the two extracted categories. The former included the five subcategories of concerns about pregnancy complications, concerns about the parenting process, concerns about the couple's relationship, fear of Covid-19, and occupation-related stress. The latter included the three subcategories of unpleasant feelings, current pregnancy experiences, and previous pregnancy experiences. Conclusions: This study highlighted a wide range of psychosocial factors involved in the PD of women with HRP. These findings can be used to design appropriate prevention strategies to manage the mental health problems of these women in order to turn their pregnancy into a pleasurable experience.